Customers' attitude towards Automated Teller Machines (ATM) in banks operating in Libya A study on banks operating in the eastern region - El-Kailany, Adel; Abdullah Ahmad (Journal of Pure & Applied Sciences, 2024)
Technology today plays an important role in the banking services market, and Automated Teller Machines ATM is one of the technological innovations that contributed to the spread and reduction of banking services costs. The ATM performs many deposit and withdrawal services and other banking services. Although automated teller machines ATM had a role in reducing the costs of banking transactions, increasing the efficiency of banking work by relieving work pressure on employees in the banking sector, and increasing the speed of completion of transactions. However, there are many customers in Libya who see that the services provided by these devices are not at the required level, and that there are many problems they face while dealing with them, such as the large number of malfunctions, the lack of a sufficient number of them, and the long wait to reach the machine. Thus, this study aims to identify the attitude of customers towards the services provided by ATM devices, and the factors that affect the attitude of customers towards these machines. The study relied on the quantitative method, and the study relied on the questionnaire tool to collect data from clients, where 126 questionnaires were analyzed using the SPSS 23 program on the target sample. The study found that customers of Libyan banks have a somewhat positive attitude towards the use of ATMs, and there are no statistically significant differences in the attitudes of customers towards using ATMs based on their demographic characteristics (gender, age, educational level, occupation, income). The study recommends the need to pay attention to the deployment of automated teller machines, especially that there is a good awareness of ease of use, as this has an impact on solving the liquidity problem experienced by Libyan banks.